2012
DOI: 10.1097/iop.0b013e31821639cc
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Upper Eyelid Retraction Caused by Topical Bimatoprost Therapy

Abstract: The authors report a case with upper eyelid retraction caused by topical bimatoprost therapy. Topical bimatoprost 0.03% was administered to a 69-year-old woman with bilateral normal-tension glaucoma. It was first administered to the left eye, and 3 weeks later, therapy on the right side of the eye was initiated. One week after the initiation of therapy on the right side, right upper eyelid retraction occurred, and 63 days after starting treatment on the left side (42 days after initiation on the right side), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…In contrast to all other studies except for one, 16 our results revealed upper eyelid retraction-not ptosis-to be a significant feature of PAP, showing significantly greater MRD1 measurements in treated eyelids. This is not surprising because lower eyelid retraction has already been described as part of PAP and confirmed in this study, and the precise mechanism of previously reported upper eyelid ptosis in this syndrome is speculative.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…In contrast to all other studies except for one, 16 our results revealed upper eyelid retraction-not ptosis-to be a significant feature of PAP, showing significantly greater MRD1 measurements in treated eyelids. This is not surprising because lower eyelid retraction has already been described as part of PAP and confirmed in this study, and the precise mechanism of previously reported upper eyelid ptosis in this syndrome is speculative.…”
Section: Discussioncontrasting
confidence: 86%
“…[29][30][31] Since the initial report by Peplinski and Smith, many case series have assessed the effects of PGA use on the ocular adnexa, none of which produce consistent and reproducible orbital and adnexal measurements that fully quantify and qualify PAP. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Most of these studies were based on either patient or family member's complaints. Interestingly, only 27% of our subjects noticed changes in their eyelids since beginning PGA therapy, and only 15% of these were bothered by these alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential link between topical prostaglandin analogue use and eyelid malposition, both retraction and ptosis, has been reported. [19][20][21][22][23] Typical ocular and periocular tissue effects associated with topical application of prostaglandin analogues include deepening of the upper eyelid sulcus, loss of the inferior orbital fat pads, enophthalmos, a constellation of symptoms referred to as prostaglandin-associated periorbitopathy, and upper eyelid ptosis. 19,20 A cross-sectional survey of 343 patients found that the use of bimatoprost, travoprost, or latanoprost was associated with an odds ratio of 4.04 (95% confidence interval, 2.43-6.72, p value = 7.37 E-08) for the development of worsening ptosis, defined as a decrease in MRD1 of at least 1 mm.…”
Section: The Effect Of Topical Prostaglandin Analogues On Eyelidmentioning
confidence: 99%
“…23 Theoretically, stimulation of Mueller's muscle would result in upper eyelid retraction through an increase in the supero-posterior directed force of F MM . However, a mechanism for prostaglandin-mediated activation of Mueller's muscle is not clear.…”
Section: The Effect Of Topical Prostaglandin Analogues On Eyelidmentioning
confidence: 99%